Meat Characteristic of Crossbred Local Chicken Fed Inulin of Dahlia Tuber and Lactobacillus sp. - Zakaria Husein Abdurrahman; Y. B. Pramono; N. Suthama (Media Peternakan, 2016)
This study was conducted to evaluate the meat characteristic of crossbred local chicken fed diet containing both dahlia tuber powder as inulin source and probiotic Lactobacillus sp. The experimental animals were 168 crossbred local chickens which were randomly divided into 6 groups of treatment (4 replications each) when they were 21-d old. A completely randomized design with 2 x 3 factorial pattern consisted of 2 levels of prebiotic [(0.8% (D1) and 1.2% (D2)] and 3 levels of probiotic [without probiotic (L0), 1.2 mL (L1), and 2.4 mL (L2)] was arranged in the present study. One mL probiotic (Lactobacillus sp.) was equal to 108 cfu. Results showed that the supplementation of prebiotic and probiotic significantly (P<0.05) affected breast meat color in terms of L* (lightness) and b* (yellowness). The meat fat mass and cholesterol was significantly (P<0.05) decreased by the combination of prebiotic and probiotic. The hardness of meat was not affected significantly by all treatments. The conclusion is that breast meat color could be improved, and both meat fat mass and cholesterol content could be decreased by feeding a combination of 1.2% dahlia tuber powder as inulin source and 1.2 mL probiotic Lactobacillus sp.